Unraveling ocean $$\hbox {pCO}_{2}$$ pCO 2 dynamics in Northwest Greenland Fjords - Camille Hayatte Akhoudas; Adam Ulfsbo; Brett F. Thornton; John W. Pohlman; Lee-Gray Boze; Martin Jakobsson; Christian Stranne (Scientific Reports)
Abstract We investigated the relative contributions of various factors that influence seasonal changes in sea surface partial pressure of $$\hbox {CO}_{2}$$ CO 2 ( $$\hbox {pCO}_{2}$$ pCO 2 , calculated from the measured pH and total alkalinity) in four regions of northwestern Greenland: Nares Strait, Lincoln Sea, Sherard Osborn and Petermann fjords. Using the temperature minimum layer as a proxy for winter conditions, we examined $$\hbox {pCO}_{2}$$ pCO 2 dynamics from the onset of sea-ice melt to summer. Our findings revealed significant spatial variability in $$\hbox {pCO}_{2}$$ pCO 2 , driven by differences in temperature, freshwater inputs, and biological activity. In particular, in Sherard Osborn Fjord substantial freshwater inputs and strong stratification were found to enhance $$\hbox {pCO}_{2}$$ pCO 2 accumulation, while in Petermann Fjord biological $$\hbox {CO}_{2}$$ CO 2 uptake was the main driver. This study, conducted in summer 2019, underscores the critical role of northwest Greenland’s coastal waters as a summer $$\hbox {CO}_{2}$$ CO 2 sink. It highlights the complex interplay of physical and biogeochemical processes in modulating $$\hbox {pCO}_{2}$$ pCO 2 , suggesting significant regional differences in $$\hbox {CO}_{2}$$ CO 2 dynamics between two neighboring fjords.